Musculo-skeletal and neurological aspects of Lyme disease. (1st October 2016) - Wright, Stephen
Abstract : Lyme disease can cause arthritis and radicular pain along with other neurological and cardiac problems. The article reviews present understanding of the epidemiology, transmission, diagnosis and treatment of Lyme borreliosis.